EVALUATION OF MICRONUTRIENT-DENSE POTATO GENOTYPES IN JUMLA, NEPAL - Kadian, Mohinder Singh (Potato Journal, 2017)
Malnutrition and food insecurity are the major challenges associated to livelihood of the people living in mountain region of Nepal. Potato, an important high land food crop, has a tremendous potential to address these problems. To recommend micronutrient-dense potato varieties appropriate to Jumla district, a collaborative study was undertaken on eighteen potato bred materials to evaluate the yield at Agriculture Research Station (ARS, Horticulture Farm) Rajikot (2330 masl) as an on-station whereas on-farm trials were conducted in the farmers’ field, Patmara (2360 masl) and Talium (2300 masl). Mean marketable tuber weight /plot over on-station and on-farm trials in both the years was highest (9.2 kg) in clone CIP 395112.32 and total tuber number/plant was highest in Jumla Local and Kufri Jyoti. The average marketable yield over on-station and on-farm experiments and years recorded higher in clone CIP 393073.179 (22.6 t/ha) and Kufri Jyoti (22.1 t/ha). CIP 395112.32 and CIP 394611.112 produced the average higher yield (21.7 and 20.4 t/ha, respectively) than Jumla Local and Desiree. CIP 393073.179, CIP 395112.32, CIP 394611.112 and Kufri Jyoti found better in average marketable yield over the on-station and on-farm experiments. Participatory evaluation of organoleptic traits exhibited that the tubers of CIP 393073.179, CIP 395112.32 and CIP 394611.112 had acceptable quality in appearance, taste and texture. These clones can be recommended to farmers for production which would help to solve the nutrition and food insecurity problem.